PARAGEN 1.0: A Standardized Synthetic Gene Library for Fast Cell-Free Bacteriocin Synthesis - Gabant, Philippe; Borrero, Juan (Frontiers in Bioengineering and Biotechnology, 2019)
The continuous emergence of microbial resistance to our antibiotic arsenal drugs is widely becoming recognized as an imminent threat to global human health. Bacteriocins are antimicrobial peptides currently under consideration as real alternatives or complements to common antibiotics. These peptides have been highly studied, novel bacteriocins are regularly reported and several genomic databases on these peptides are currently maintained. Despite this, to our knowledge, a physical collection of bacteriocins that would allow testing and comparing them for different applications does not exist. Rapid advances in synthetic biology in combination with cell-free protein synthesis technologies offer great potential for fast protein production. Based on the amino acid sequences of the mature peptide available in the databases, we have built a bacteriocin gene library, called PARAGEN 1.0, containing all the genetic elements required for in vitro cell-free peptide synthesis. Using PARAGEN 1.0 and a commercial kit for cell-free protein synthesis we have produced 164 different bacteriocins belonging to the class II (unmodified bacteriocins) group. Of the bacteriocins synthesized, 60% have shown antimicrobial activity against at least one of the indicator strains tested, including Gram-positive and Gram-negative bacteria representing commonly used lab strains, industrially relevant microorganisms, and known pathogens. This bacteriocin collection represents a streamlined pipeline for selection, production, and screening of bacteriocins as well as a reservoir of ready-to-use antimicrobials against virtually any class of relevant bacteria.